TRANSFORMASI BENTUK GEOMETRIS - Ridwan Lufti (Institut Seni Indonesia Yogyakarta, 2017)
Geometric Transformation are obtained from triangular symbol/ icon of lamp in an electricity installation diagram, which designed prior to assembly/ installation of electricity in a building/ location. These geometric (symbols) transformation when transformed onto artworks, will bring diverse possibility of new formation. The purpose of this geometric transformation (from the triangular symbols in electricity) is to explore how artistic the new triangular shape in context of artworks. The triangular shape took as the basic of exploration and experiment in this printmaking artworks, enhanced with light and motion.Keywords: Transformation, Geometrical shape, Light and motion, Electricity installation.